2021
DOI: 10.1002/nop2.751
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with aggressive behaviour in persons with cognitive impairments using home care services: A retrospective cross‐sectional study

Abstract: Aim This study aimed to investigate the frequency of documented aggression, on the part of cognitively impaired individuals, against health professionals in home care services and to highlight related factors. Design A retrospective cross‐sectional study was conducted using data obtained from the nursing documentation of six home care service organizations in Switzerland. Methods We analysed the nursing documentation of 1,186 clients in six home care services, between July 2019–September 2019, using the Cohen‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…This result hints that unguided discussions between team colleagues might increase negative feelings against the care recipient. In the light the results of Schnelli, Ott et al ( 2021 ), which disclose that staff with lower education is mostly used in the case of clients with aggressive behaviour, these insights highlight the need for guided reflexive processes. Guided reflexive processes such as case reviews might help reframe the aggressive incidents experienced.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This result hints that unguided discussions between team colleagues might increase negative feelings against the care recipient. In the light the results of Schnelli, Ott et al ( 2021 ), which disclose that staff with lower education is mostly used in the case of clients with aggressive behaviour, these insights highlight the need for guided reflexive processes. Guided reflexive processes such as case reviews might help reframe the aggressive incidents experienced.…”
Section: Discussionmentioning
confidence: 93%
“…Investigations in the home care settings show that aggressive behaviour against professional caregivers occur often in the home care setting as well (Hanson et al, 2015 ; Schablon et al, 2018 ). Schnelli, Ott, et al ( 2021 ) found that 14.8% of clients availing home care services display verbally or physically aggressive behaviour towards caregivers and that such behaviours were linked to cognitive impairment. Home care services have gained importance due to demographic changes worldwide (Genet et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Les soins à domicile doivent s'adapter et se développer pour répondre à ces différents changements. En Suisse, plusieurs études sur les soins infirmiers à domicile ont été menées (6)(7)(8)(9)(10)(11)(12) et d'autres recherches sont en cours. Les physiothérapeutes font partie des professionnels de santé qui interviennent au domicile des patients.…”
Section: Contexteunclassified
“…Several studies have shown that patients are often unaware of the necessity for their medication or unsure how to take their medication (Bailey et al, 2019 ; Schnelli et al, 2021 ). Therefore, systematic identification of people with limited or no ability to take responsibility for their medication therapy is critical (Gehring, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A structured and regular assessment of patients' medication literacy should be conducted to ensure that they are managing their medications appropriately (Bailey et al, 2019 ). This is especially relevant for the home care population, as patients usually suffer from several chronic diseases and 35% are cognitively impaired (Schnelli et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%